Perception of Chinese hi-tech brands in Europe - Vargasová, Nikola (2015)
The thesis "Perception of Chinese hi-tech brands in Europe" examines how Chinese origin affects the perception of hi-tech brands by European customers. The theoretical part deals with the concept of country of origin and its relationship to the concept of brand equity. The practical part is devoted to the research on the topic of perception of Chinese smartphones in Europe. The research results confirm both hypotheses: 1. Customers when choosing a smartphone brand are not affected by the country of origin. 2. European customers do not perceive Chinese hi-tech products as of low quality.